E-jing: Using Information Technology to Teach about Chinese Religions - Deitrick, Jim (Teaching theology and religion, 2008)
This article discusses ways in which modern online information technologies may be used to enhance students' understanding of Chinese religions and religious texts. This discussion is predicated upon a model of linguistic communication that places significant weight on the structures and “sedimented presuppositions” of language in determining the meanings of discourse. Assignments are presented that use online technologies to give even beginning students insight into the presuppositions of Chinese religious discourse, while also allowing them to explore, kinesthetically, one of Confucianism's central practices, the reading and writing of Chinese characters. Appendices providing additional materials related to the course are available online: http://www.wabashcenter.wabash.edu/journal/article2.aspx?id=14153.